Real-world carbon emissions evaluation for prefabricated component transportation by battery electric vehicles - Haining Wang; Hong Zhang; Liang Zhao; Zhixing Luo; Keming Hou; Xiaoxuan Du; Zhaolin Cui; Yiqing Lu (Energy Reports, 2022)
As the first and second largest greenhouse gases (GHG) emissions industries, the sustainable development of construction and transportation industry determines the future of human society. The current carbon emission calculation standard does not cater to electrical transportation, as well as the characteristics of prefabricated components comparing with raw materials. This study focused on the transportation process of prefabricated components, exploring the characteristics of battery electric vehicles (BEV) in carbon emissions. Through the real-world experimental research, the true carbon emissions performance of components’ transportation was obtained under different external parameters. After preliminary screening of variables through correlation analysis, several variables were determined as compensation coefficient for multiple linear regression. The quantitative relationship between the three parameters of Load Ratio, Average Speed and Atmospheric Temperature on carbon emissions factor was revealed, and the R2 value of the fitting formula reached 0.7079(AC off). Results shows that BEV can reduce GHG emissions by 36.18%–54.69%. As well as promote the low-carbon innovation of the fabricated construction industry.